2013
DOI: 10.1186/1746-6148-9-54
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vascular smooth muscle cells in canine great vessels

Abstract: BackgroundElucidating the histological characteristics of normal vascular smooth muscle cells (VSMCs) is important for understanding mechanisms of development, disease etiology and the remodeling and/or regeneration process of the vessel. However, knowledge regarding VSMCs is focused primarily on the artery. Although the characteristics of each great vessel are documented, few studies have examined VSMCs in parallel within each great vessel. The present study focused on comparing characteristics of canine VSMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Approximately 10–15 ml of angiographic agent was injected to evaluate the features of the iTEV, IVC, and HV with breath-holding to avoid respiratory fluctuation. No anticoagulants were administered until euthanasia was performed [ 1 5 , 10 ]. All angiographic data were saved to digital devices for further analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 10–15 ml of angiographic agent was injected to evaluate the features of the iTEV, IVC, and HV with breath-holding to avoid respiratory fluctuation. No anticoagulants were administered until euthanasia was performed [ 1 5 , 10 ]. All angiographic data were saved to digital devices for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported the usefulness of a tissue-engineered graft (TEG) created with a biodegradable scaffold to accomplish vascular continuity in animal models [ 1 5 ] and clinical applications [ 6 9 ]. Implanted biodegradable materials act as templates for invasive cells from surrounding tissues, seeded cells, and/or newly generated tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet distinct physiological requirements, different regions of the vasculature exhibit different physical properties. Early studies have shown that the VSMCs of the proximal large vessels (which comprises the arch of the aorta, the common carotids, the common pulmonary trunk, and the brachiocephalic artery) are derived from the neural crest (NC) (ectomesenchymal smooth muscle) [5,6], while VMSCs of the distal vessels (which includes the abdominal aorta and the right and left carotid arteries) are derived from the mesenchyme [7,8]. At the region of the interface of these vessels, VSMCs are derived from mixed origins, both of the ectomesenchymal and mesenchymal.…”
Section: Origin Of Vsmcsmentioning
confidence: 99%
“…Not surprisingly, relevant differences exist amongst the same cell type (EC or VSMC) within the separate vascular beds. A study comparing canine VSMCs within the aorta (Ao), branch pulmonary artery (bPA), main pulmonary artery (mPA) and inferior vena cava (IVC) revealed not only obvious histologic differences in layer thickness and cellular organization, but also significant protein expression differences with regards to smooth muscle actin (SMA), myosin heavy chain (MHC) and smooth muscle myosin heavy chain isoform 2 (SM2) [ 30 ].…”
Section: Anatomical Proximity Of Ec and Vsmcmentioning
confidence: 99%